Artificial intelligence and analysis of body position to determine the speed of the strike in Karate - Dr Mohammed Ghazi (Inspiree)
The  purpose  of  the study. The techniques of artificial intelligence in educational hardware and software are able to deduce knowledge and skills, and the importance of the study is due to the use of artificial intelligence techniques in analyzing the situation of skill performance, the use of artificial intelligence techniques in the system of skill analysis of the skills under study, the link of artificial intelligence with kinetic variables For the skills under study and the study aimed to apply artificial intelligence techniques in skill analysis, building an artificial intelligence system from motor variables and motor performance.